The American - Britton, Andrew (New York : Kensington Books, 2006)
CIA agent Ryan Kealey, along with British-born agent Naomi Kharmai, must track former U.S. soldier Jason March, an assassin who has aligned himself with a Middle Eastern terrorist network determined to destroy the United States.
National College of Business and Arts
Keywords: Intelligence officers -- Fiction; Detective and mystery fiction